The Mediating Role of Psychological Distress in Excessive Gambling among Young People: A Four-Country Study - Vuorinen, Ilkka (Int J Environ Res Public Health, 2021)
Background and aims: Loneliness and a low sense of mastery are associated with excessive gambling, but the underlying processes of these relationships remain unstudied. Because psychological distress can increase vulnerability to excessive gambling, we investigated its mediating role in these relationships among young people. To meet the need for cross-country research, we also observed how these relationships occur in four countries with different cultures. Design, setting, and participants: Demographically balanced cross-sectional survey data were collected from 15–25-year-olds in Finland (n = 1200; 50% male), the United States (n = 1212; 49.8% male), South Korea (n = 1192; 49.6% male), and Spain (n = 1212; 51.2% male). Measurements: Excessive gambling was measured with the South Oaks Gambling Screen, psychological distress was assessed with the 12-item General Health Questionnaire, loneliness was measured with the three-item Loneliness Scale, and low sense of mastery was assessed with the Pearlin Mastery Scale. Associations were examined first using zero-inflated negative binomial regression analyses with excessive gambling as the outcome. In addition, path analyses were performed to study how loneliness and low sense of mastery relate to excessive gambling, with psychological distress as the mediating variable. Findings: Loneliness and low sense of mastery were associated indirectly with excessive gambling via psychological distress in all country samples. Low sense of mastery was also directly associated with excessive gambling. There was a direct association between loneliness and excessive gambling only in samples from South Korea and Spain. Conclusions: Psychological distress is an important factor in understanding how loneliness and sense of mastery relate to gambling.